Analisis Bilirubin dan Hemoglobin Pada Bayi Baru Lahir - Pratama, Ridho; Khofifah, Nuriah; Armah, Zulfian; Rafika, Rafika (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2022)
One of the causes of infant death outside the womb is hyperbilirubinemia. This hyperbilirubinemia is a clinical phenomenon often found in newborns in the first week of life. In laboratory examination, the determination of hemoglobin level is an indicator that is widely used to determine the prevalence of anemia. This study uses an observation method with a descriptive approach. The data collection of this research was carried out at RSIA Pertiwi Makassar City in May 2021. The sample in this study was secondary data for all newborns. The results of this study were obtained from 40 newborns (85%) who had hyperbilirubinemia. As many as 6 newborns (15%) did not have hyperbilirubinemia while from 25 newborns, 9 newborns (36%) had anemia, and as many as 16 newborns. Born (64%) did not have anemia. Keywords: Bilirubin, Hemoglobin, And Newborn